A Critical Assessment of Heinz Halm’s Views on the Fatimid Caliph of Egypt al-Hākim bi-Amr Allāh - Ansari, Raziyeh; Chelongar, Mohamad Ali (Journal of Al-Tamaddun, 2023)
Al-Hākim bi-Amr Allāh (reign 996–1021), the sixth Fatimid caliph in North Africa, is one of the most controversial characters in the history of Islam, who has engendered different and sometimes conflicting views of historians. Adopting a descriptive–analytical method, the present study aimed to assess the views of Heinz Halm, the contemporary Ismaili era researcher, on al-Hākim. Although al-Hākim has gone down the history as a brutal, wicked-minded man, Halm in The Fatimids and Their Traditions of Learning (1997) refers to al-Hākim as a highly-respected person among Egyptians, as a person who had a stable character with consistency in religious policies. Moreover, Halm depicts al-Hākim as totally opposed to the Druze who emerged, as a religious sect, with a belief in al-Hākim’s divinity. The results of the study showed that Halm, drawing eclectically on historical sources, reports, and statements to depict al-Hākim’s character as justified and sound, had foregrounded, marginalized, and eliminated historical data about al-Hākim.